Use of wheat, triticale and rye flours in layer cake production - Oliete, Bonastre (2010)
In this study, the capacity of obtaining high quality layer cakes from rye and triticale lines was analysed and compared to wheat lines. The samples were characterised considering grain hardness, flour composition and quality parameters as protein, pentosan, damaged starch, pasting viscosity and functional predictive test - solvent retention capacity test. Cakes were analysed in weight, symmetry, volume, volume index (VI) by measuring the height in different points of the cake, crust and crumb colour, crumb structure and texture. Wheat and triticale cakes showed similar characteristics. Rye cakes showed higher volume and lower weight than those with crumbs darker in colour, higher adhesiveness, springiness and resilience. The multiple regression analysis was used to develop an equation for cake volume index prediction. The best-fit linear regression model was: VI = 14.75 - 0.14 protein + 0.93 water soluble pentosan - 0.27 total pentosan. Despite the differences, high quality cakes can be elaborated with rye, triticale and soft wheat cultivars. © 2010 The Authors. Journal compilation © 2010 Institute of Food Science and Technology.